Perfect liberty - Castle, Clara Francelia (My University, 1894)
Introduction: Man early shared the love of greater gain, which generated oppression and bondage. The question of liberty has been the thought and highest interest of the nations. Much study has been put upon the beginnings and growth of liberty; and to understand its nature, has been the desire of man. Often, for the best growth of liberty, there must be revolution and bloodshed, before it can be fully established. The settlement of the colonies, the separation from England, and the civil war, examples of revolution that were necessary, for the higher advancement of liberty. Individual and civil liberty are closely connected. Religion, society, and custom, may be transformed into a yoke that binds. The final triumph, when perfect liberty will exist.
Citation: Castle, Clara Francelia. Perfect liberty. Senior thesis, Kansas State Agricultural College, 1894.
Morse Department of Special Collections
Keywords: Liberty; Government; Parliament; Political science; Civics; Theses; Manuscripts (documents)